Malawi : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This report highlights the growth and macroeconomic policies in Malawi, and also analyzes the interaction between aid flows and macroeconomic stabilization policy. The paper reviews the country's recent trade reform program and summarizes other associated reforms and changes in the pattern of trade. It provides a survey of selected studies on the direct impact of HIV/AIDS on mortality and morbidity, measures of their possible effects on output, growth, and the fiscal position, and also a statistical appendix is provided for the country.